Skrining Fitokimia dan Aktivitas Antioksidan Fraksi Etanol Alga Merah Eucheuma spinosum - Sari, Bina Lohita; Susanti, Nurulia; Sutanto, Sutanto (Pharmaceutical Sciences and Research, 2015)
The red alga, Eucheuma spinosum from South Bangka Waters was shown to contain antioxidant activity. Natural antioxidants from algae are known to play an important role against various diseases and aging processes. The study objective was to investigate phytochemical screenings and antioxidant activity of ethanol fractions Euchema spinosum from south Bangka waters. Antioxidant activities of fresh algae (FA), dry algae (DA), and algae product (AP) were determined with DPPH (1,1-diphenyl-2-picrylhydrazyl) assay. Extraction was conducted using 70% ethanol in acidic environment for 24 hours. Then, the extract was evaporated using rotary evaporator. Dry extract was fractionated with ethanol - n - hexane ( 2 : 3 ) and the ethanol fraction was dried. The phytochemical screenings showed that all fractions had flavonoid, alkaloid and triterpenoid compounds. The most potent antioxidant activity was found in the ethanol fraction of AP with IC50 value 333.66 μg/mL, FA 418.32 μg/mL and DA 472.14 μg/mL. Based on the results, it can be concluded that the ethanol fraction of algae product can be used as a antioxidant source.